Influence of sleep disorders on the behavior of individuals with autism spectrum disorder - Fadini, Cintia C. [UNESP] (2015)
The aim of this study was to investigate the correlation between sleep disorders and the behavior of subjects with autism spectrum disorder (ASD) and control subjects using specific questionnaires. A small percentage (1.8%) of the control subjects had symptoms indicative of sleep-breathing disorders (SBD) and nocturnal sweating. Fifty-nine percent of the subjects with ASD had symptoms indicative of at least one sleep disorder, with SBD the most commonly reported (38%). In the control group, the symptoms of SBD were correlated with social, thought, attentional, aggression, externalizing and behavioral problems. In the ASD group, disorders of arousal (DA) were correlated with thinking problems, and disorders of excessive somnolence were correlated with thinking and behavioral problems. These results suggest that children and adolescents with ASD have a high frequency of sleep disorders, which in turn correlate with some of the behavioral traits that they already exhibit. Furthermore, sleep disturbances, when present in the typically developing children, also correlated with behavioral problems.